Analisis Gangguan Hubung Singkat dan Koordinasi Proteksi di Jaringan 20 KV PLTD Aneuk Laot ULP Sabang Dengan Simulasi ETAP 21.0.1 - Firman Hakiki; Adi Sastra Pengalaman Tarigan; Hamdani (Jurnal Nasional Teknologi Komputer, 2025)
Electricity plays a vital role in human life, so serious efforts are needed to ensure its reliable distribution. One of the main issues in electrical systems is short-circuit faults, which can cause equipment damage and widespread power outages. To minimize the impact of such faults, a protection system that is reliable, adequate, and well-coordinated is essential. A good protection system must meet several criteria, such as proper selectivity, the ability to quickly respond to disturbances to reduce equipment damage, high sensitivity to detect even the smallest faults based on regulated current levels, and efficient coordination and backup in case the main protection fails. It must also remain stable against external disturbances. To achieve reliable protection coordination, simulation is necessary. One tool that can be used is ETAP 21.0.1 software. ETAP helps in modeling the electrical network, calculating short-circuit currents, and evaluating the performance of primary and secondary protection coordination. The simulation results show that short-circuit current values vary at each busbar point depending on the system impedance and network configuration. Through this simulation, settings like the Time Multiplier Setting (TMS) and pickup current can be adjusted to improve relay coordination, making it more selective and reliable. This study provides valuable insight into the reliability and safety of the electricity distribution operating system in the Sabang ULP area.